Modals and Modality in English - Inchaurralde Besga, Carlos (Miscelánea: A Journal of English and American Studies, 1995)
Modality as a linguistic notion has a clear expression in English through the use of different modal verbs. In this respect, we can approach this fact from both a diachronic and a synchronic perspective. In the development of modals in time, it is interesting to consider Bernd Heine's account, for whom modals' development should be considered within a process of grammaticalization and desemantization of full verbs, fully explainable in cognitive terms. From a synchronic point of view, modality as is expressed by English modals should be viewed in connection with tense and aspect. A convenient way of visualizing the interplay that takes place is the use of Minkowsky's space-time cones, which are presented here with examples illustrating the usefulness of this model for the description of these grammatical notions in an integrated manner.